A Phonemic Analysis Between English And Indonesian In English Conversation - Madya Ramadhani; Roni Ripaldi Turnip; Anita Sitanggang (CV Putra Publisher, 2023)
This study compares and contrasts the phonetic systems of English and Indonesian in the